Sinergi Akademisi, Pokdarwis, dan Komunitas Pecinta Sungai dalam Pemetaan Potensi Wisata Tukad Lilaulangun - Muhamad Nova; I Made Budiasa; I Wayan Basi Arjana; Cokorda Istri Sri Widhari (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Kesiman Village has an urban tourism potential that can attract visitors to enjoy recreational activities with their families. This tourism potential is located at Tukad Lilaulangun Kebonkori, situated behind the Kebonkuri Lukluk community hall (balai banjar). Tukad Lilaulangun is currently being developed as a regional icon by the Kesiman Village administration. However, based on initial observations and preliminary interviews, it was identified that Tukad Lilaulangun does not yet have a fixed agenda or tourism attractions that can draw both local and international tourists to visit. On the other hand, community education regarding the importance of maintaining river cleanliness and sustainability remains insufficient. Therefore, technological integration is needed to deliver environmental campaigns effectively to people across generations. In response to these challenges, the Department of Tourism at Bali State Polytechnic contributed through a community service program aimed at mapping the area’s tourism potential. This program was carried out in several stages, including socialization, digital marketing training, tourism potential mapping, and focus group discussions. The methods applied involved outreach activities, face-to-face material delivery, and direct practical implementation. Three activities were successfully conducted, resulting in an average partner satisfaction score of 3.22 (satisfied) in the preparation stage, 3.30 (very satisfied) during implementation, and 3.21 (satisfied) in the evaluation stage. These results indicate a strong alignment between the partner’s challenges and the solutions that have been implemented.